1996
DOI: 10.1136/bmj.313.7059.724
|View full text |Cite
|
Sign up to set email alerts
|

Information needs of cancer patients in west Scotland: cross sectional survey of patients' views

Abstract: Objective-To assess the needs of patients with cancer for information about their condition.Design-Cross sectional survey of patients' views by means of semistructured interview with questionnaire.Setting-A regional cancer centre and two university hospitals in west Scotland.Subjects-250 (93%) of 269 cancer patients invited to participate in study who were selected by age, sex, socioeconomic status, and tumour site to be representative of cancer patients in west Scotland.Main outcome measures-Patients' need to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

20
310
3
20

Year Published

1998
1998
2004
2004

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 499 publications
(353 citation statements)
references
References 9 publications
(10 reference statements)
20
310
3
20
Order By: Relevance
“…Even though both the verbal and written information on the first subject was more comprehensive than for the apparently more straightforward concept of nonrandomised treatment, this comprehensiveness may be requested by the patients. This concept of comprehensive information is in accordance with a study on 250 patients at an oncology centre in Scotland, which showed that 79% of patients wanted as much information as possible (Meredith et al, 1996). The proportion of patients who wanted to know the chance of cure and the side effects of therapy was 91 and 94%, respectively.…”
Section: Resultssupporting
confidence: 75%
See 1 more Smart Citation
“…Even though both the verbal and written information on the first subject was more comprehensive than for the apparently more straightforward concept of nonrandomised treatment, this comprehensiveness may be requested by the patients. This concept of comprehensive information is in accordance with a study on 250 patients at an oncology centre in Scotland, which showed that 79% of patients wanted as much information as possible (Meredith et al, 1996). The proportion of patients who wanted to know the chance of cure and the side effects of therapy was 91 and 94%, respectively.…”
Section: Resultssupporting
confidence: 75%
“…No differences were noted among patients informed about randomised or nonrandomised experimental treatments. Bennett and Alison, 1996), and surveys have shown that patients want a high degree of information and the information usually produces a positive effect (Fallowfield et al, 1995;Meredith et al, 1996). Others have pointed out that the information needs to be individualised , and also the expectations of the patients have been evaluated in relation to satisfaction with the consultation (Brown et al, 1997).…”
Section: Resultsmentioning
confidence: 99%
“…This study reinforces data from the west of Scotland (Meredith et al, 1996) and the large survey of Jenkins et al (2001), which show that most cancer patients want as much information as possible. This is also true of Asian patients in Leicestershire.…”
Section: Discussionsupporting
confidence: 88%
“…Many patients had more than one treatment modality. Patients' views about information were elicited by a questionnaire widely used in the past (Cassileth et al, 1980;Jenkins et al, 2001) and modified in the light of experience in the west of Scotland (Meredith et al, 1996). It consisted of two parts, one of which described their general preference for information.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation